Structural reliability of existing rc beams strengthened with UHPFRC tensile layers - Lenganji Simwanda; Nico De Koker; Celeste Viljoen; Adewumi John Babafemi (Acta Polytechnica CTU Proceedings)
A methodology for reliability analysis of reinforced concrete (RC) beams strengthened with ultra high-performance fibre reinforced concrete (UHPFRC) tensile layers is presented. The proposed methodology includes stochastic stress-block analysis of a section, assuming a perfect bond between the RC beam and the UHPFRC layer. Annual reliability analysis of the RC beam before and after the strengthening operation is conducted. Deterioration induced by chloride corrosion is incorporated into the analysis via a chloride induced corrosion model based on Fick’s law of diffusion and described stochastically to account for the epistemic uncertainty in the time to corrosion initiation and rate of corrosion. A plot for determining the required thickness of the UHPFRC tensile layer to upgrade to the required reliability level is also given, considering the time from construction to when the strengthening operation is conducted. The proposed approach is easy to apply for routine practice.